Toxicokinetics of ibogaine and noribogaine in a patient with prolonged multiple cardiac arrhythmias after ingestion of internet purchased ibogaine. (3rd July 2017) - Henstra, Marieke; Wong, Liza; Chahbouni, Abdel; Swart, Noortje; Allaart, Cor; Sombogaard, Ferdi
Abstract: Background: Ibogaine is an agent that has been evaluated as an unapproved anti-addictive agent for the management of drug dependence. Sudden cardiac death has been described to occur secondary to its use. We describe the clinical effects and toxicokinetics of ibogaine and noribogaine in a single patient. For this purpose, we developed a LC-MS/MS-method to measure ibogaine and noribogaine plasma-concentrations. We used two compartments with first order absorption. Case details: The maximum concentration of ibogaine was 1.45 mg/L. Our patient developed markedly prolonged QTc interval of 647ms maximum, several multiple cardiac arrhythmias (i.e., atrial tachycardia and ventricular tachycardia and Torsades des Pointes). QTc-prolongation remained present until 12 days after ingestion, several days after ibogaine plasma-levels were low, implicating clinically relevant noribogaine concentrations long after ibogaine had been cleared from the plasma. The ratio k12 /k21 for noribogaine was 21.5 and 4.28 for ibogaine, implicating a lower distribution of noribogaine from the peripheral compartment into the central compartment compared to ibogaine. Conclusions: We demonstrated a linear relationship between the concentration of the metabolite and long duration of action, rather than with parent ibogaine. Therefore, after (prolonged) ibogaine ingestion, clinicians should beware of long-term effects due to its metabolite.